Differential diagnosis of acute respiratory infections in mixed circulation - Zh. B. Ponezheva; A. N. Turapova; A. R. Marzhokhova; S. B. Yatsyshina; Yu. N. Khlypovka; А. A. Ploskireva (Лечащий Врач)
Acute respiratory infections are the most common group of infectious diseases characterized by pronounced tropism to the respiratory tract. Acute respiratory infections has occupied a leading place in the structure of infectious and parasitic diseases for decades. The high prevalence of diseases, the presence of adverse outcomes and complications, the difficulty of diagnosis and the choice of an individual treatment strategy making relevant the problems of an associated with acute respiratory tract infections. The review article describes in detail the features of manifestations of acute respiratory infections of viral etiology, occupying up to 80% of all cases in the epidemic season (influenza, parainfluenza, adenoviruses, rhinoviruses, respiratory syntial virus, coronaviruses, metapneumovirus, bokavirus). The characteristics and severity of the course of acute respiratory tract infections of bacterial etiology (Streptococcus pneumoniae, Haemophilus influenzae, Mycoplasma pneumoniae, Chlamydophyla pneumoniae, Streptococcus pyogenes) are also presented. The features of various clinical manifestations of circulating respiratory infections are analyzed. The features of nosological forms in acute respiratory infections are presented. Risk factors for the unfavorable course of acute infections pathways to the respiratory tract were noted. Modern methods of laboratory diagnostics of acute respiratory infections are described, illustrated in a convenient algorithm. The necessity of early etiological verification of acute respiratory infections for the timely appointment of adequate therapy, which reduces the risk of severe course and complications, is also emphasized. Thus, the similarity of clinical manifestations of acute viral infections of the respiratory tract, especially with the simultaneous circulation of various respiratory viruses during the ongoing COVID-19 pandemic, requires mandatory laboratory verification of the pathogen for timely etiotropic therapy and prevention of the spread of infection, as well as timely anti-epidemic measures.